Water uptake of apple trees in the Alps: Where does irrigation water go?. Issue 6 (23rd June 2021) - Penna, Daniele; Zanotelli, Damiano; Scandellari, Francesca; Aguzzoni, Agnese; Engel, Michael; Tagliavini, Massimo; Comiti, Francesco
Abstract: Understanding root water uptake sources in agricultural systems is becoming increasingly important in the sustainable management of water resources under changing climatic conditions. In this work, a stable isotope approach was adopted to investigate water sources accessed by apple trees in two orchards growing in two different locations in the upper Etsch/Adige valley (Eastern Italian Alps). We tested the general hypothesis that soil water, composed of a mixture of rain and irrigation water, was the main source for tree transpiration in both fields, but trees could also access groundwater according to the different proximity to the groundwater table of the two orchards. Our results revealed that apple trees during the 2015 and 2016 growing seasons relied mostly on soil water present in the upper 20–40 cm of soils, with an apparently negligible contribution of groundwater, irrespective of the field location in the valley bottom. The isotopic composition of xylem water did not reflect irrigation water composition (or that of groundwater) but rather of rainfall and throughfall, and soil water. We related this behaviour to the intense rate of soil evaporation during the growing period that modified the original isotopic signature of irrigation water in the shallower layers, masking its actual contribution. This work contributes to improving the understanding of water uptake strategies in Alpine apple orchards and paves the way for further analysis on the proportion of irrigation and rainwater used by apple trees in mountain agroecosystems.